Discursos ambientales : una mirada histórica a la configuración del territorio del PNN Katíos en Colombia y su zona de amortiguación (2012)
ABSTRACT: This paper attempts to identify and characterize, from a historical perspective, “the environmental discourses” that have been created and have circulated on what we now know as National Parks in Colombia, specifically on the PNN Katios National Park. The research argues that such discourses have been constructed, propagated, institutionalized and legitimized as a means and dynamic factor in a broader discourse we have called “development discourse.